1986
DOI: 10.1111/j.1365-2559.1986.tb02518.x
|View full text |Cite
|
Sign up to set email alerts
|

Primitive neuroectodermal (neuroepithelial) tumour of soft tissue of the neck in a child: demonstration of neuronal and neuroglial differentiation

Abstract: A 4-year-old girl had a pathologically proven primitive neuroectodermal (neuroepithelial) tumour of soft tissue in the left posterolateral aspect of the neck. The neoplasm consisted of primitive neuroepithelial cells forming Homer Wright rosettes, mature ganglion cells and astrocytes. Astroglia were identified by localization of cytoplasmic glial fibrillary acidic protein (GFAP). Striking similarity is noted between the current tumour and those found in the central nervous system, including cerebellar medullob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

1989
1989
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…Its presence has also been reported in some primary extraneuraxial primitive neuroectodermal tumors arising in the soft tissue 11 31, orbit [ 141, and ovary [15] as well as in the primitive neuroectodermal component of the ectomesenchymomas of the thigh [16] and the parapharynx [12].…”
Section: Resultsmentioning
confidence: 88%
“…Its presence has also been reported in some primary extraneuraxial primitive neuroectodermal tumors arising in the soft tissue 11 31, orbit [ 141, and ovary [15] as well as in the primitive neuroectodermal component of the ectomesenchymomas of the thigh [16] and the parapharynx [12].…”
Section: Resultsmentioning
confidence: 88%
“…Fibrosarcoma or malignant peripheral nerve sheath tumors, small cell undifferentiated carcinomas, and carcinoid tumors may resemble some areas within the lesions. It is known that tumors of neural crest origin can show bidirectional or multidirectional differentiation 7-9…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, glial, ependymal, cartilaginous, and epithelial elements, though rare, have been found associated within pPNET 7-9. Hachitanda et al11 reported a case of pPNET with epithelial and glial differentiation, and they suggested that the neoplastic neuroectodermal tissue can display a spectrum of differentiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The same holds true for the malignant small cell tumor of the thoracopulmonary region (ASKIN et al 1979) which is now widely accepted as a clinical and topographic variant of MPNT. Several synonyms have been proposed for MPNT including neuroepithelioma (BAILEY and CUSHING 1926), peripheral neuroepithelioma (PN) (STOUT 1918), primitive neuroectodermal tumor (neuroblastoma) (NESBITT and VIDONE 1976), primitive neuroectodermal tumor (LIEBERMANN 1979), malignant neuroepithelioma (peripheral neuroblastoma) (HASHIMOTO et al 1983), primitive neuroectodermal (neuroepithelial) tumor of soft tissue (SHUANGSHOTI 1986), and peripheral neuroectodermal sarcoma of soft tissue (LLOMBART-BosCH et al 1989). Very often, no clear distinction is made between primitive peripheral neuroectodermal tumors (PPNETs) and the central counterparts (PNETs in the more common clinical sense), which may cause considerable confusion in diagnosis and treatment.…”
Section: Definitionmentioning
confidence: 99%